Measurement of hard double-parton interactions in W(→ℓν) + 2-jet events at √s = 7 TeV with the ATLAS detector - Alonso, Francisco (2013)
The production of W bosons in association with two jets in proton–proton collisions at a centre-of-mass energy of √s = 7 TeV has been analysed for the presence of double-parton interactions using data corresponding to an integrated luminosity of 36 pb−1, collected with the ATLAS detector at the Large Hadron Collider. The fraction of events arising from double-parton interactions, f (D) DP , has been measured through the pT balance between the two jets and amounts to f (D) DP = 0.08±0.01 (stat.)±0.02 (sys.) for jets with transverse momentum pT > 20 GeV and rapidity |y| < 2.8. This corresponds to a measurement of the effective area parameter for hard double-parton interactions of σ eff = 15±3 (stat.) +5 −3 (sys.) mb.